2009
DOI: 10.1016/j.ympev.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary pattern and process within the Vertigo gouldii (Mollusca: Pulmonata, Pupillidae) group of minute North American land snails

Abstract: A phylogenetic analysis of 19 sibling taxa in the Vertigo gouldii group was conducted on 73 individuals sampled across North America using DNA sequence data of the mitochondrial genes cytochrome oxidase subunit 1 (CO1) and 16S ribosomal RNA (16S), and the internal transcribed spacer-2 of the nuclear ribosomal RNA (ITS-2) gene. The results of these analyses were found incongruent with previous taxonomic concepts used to define the V. gouldii group and its composite taxa that were based entirely on conchological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…According to the phylogenetic analysis and p-distance values for COI, the studied Pseudamnicola populations can be assigned to 16 clades, most of which are probably distinct species, according to the GMYC and ABGD analysis. The GMYC procedure has been applied in several previous studies Papadopoulou et al 2009a, b;Adolfsson et al 2010;Pagès et al 2010;Powell et al 2011;Vuataz et al 2011), including some on molluscs (Nekola et al 2009;Lorion et al 2010;Jörger et al 2012;Jörger and Schrödl 2013). Reliability of species delimitated by GMYC has also been discussed in the literature (e.g.…”
Section: Molecular Phylogeny and Putative Species Delimitationmentioning
confidence: 99%
“…According to the phylogenetic analysis and p-distance values for COI, the studied Pseudamnicola populations can be assigned to 16 clades, most of which are probably distinct species, according to the GMYC and ABGD analysis. The GMYC procedure has been applied in several previous studies Papadopoulou et al 2009a, b;Adolfsson et al 2010;Pagès et al 2010;Powell et al 2011;Vuataz et al 2011), including some on molluscs (Nekola et al 2009;Lorion et al 2010;Jörger et al 2012;Jörger and Schrödl 2013). Reliability of species delimitated by GMYC has also been discussed in the literature (e.g.…”
Section: Molecular Phylogeny and Putative Species Delimitationmentioning
confidence: 99%
“…Pilsbry (1948) took a conservative approach to species designations, and chose to lump numerous forms as subspecies until appropriate data existed to falsify these hypotheses. As a result, many species-level entities were listed by Pilsbry (1948) as subspecies, as has been recently shown within the Polygyridae (Emberton 1988), Helminthoglyptidae (Lang and Gilbertson 2010), and Vertiginidae (Nekola et al 2009). However, not all of Pilsbry's subspecies concepts appear to warrant species-level listing: examples are the minor shell variants limited to specifi c canyons within a given species range, as demonstrated not only by subspecies described within Ashmunella proxima Pilsbry, 1905 andA.…”
Section: Faunistic Enumerationmentioning
confidence: 93%
“…Native vertiginids encompass approximately 1/3 of the total global richness for the entire family (Liggia 2012) and at least 2/3 of global richness for the genus Vertigo (Nekola et al 2009), making North America a globally important biodiversity center for the group. At the site scale, the importance of this family is even greater: vertiginids represent roughly 1/3 of the species and individuals found on an average site across the continent, with regional values ranging from 56% of species and 60% of individuals on an average Alaskan site to 17% of species and 21% of individuals on an average Florida site (Nekola, unpub.…”
Section: Faunistic Summarymentioning
confidence: 99%
“…Typical V. arthuri and V. paradoxa represent ends of a grade from heavily to only weakly callused forms. Nekola and Coles (2010) continued to utilize names for the range of variation within this species that Nekola et al (2009) had discounted (synonymized). Our specimens most resemble the typical form of V. arthuri.…”
Section: Family Vertiginidae Genus Vertigo Müller 1774mentioning
confidence: 99%
“…Oughton (1948) and others until quite recently, did not treat this taxon as a separate species. However, based on analysis of mitochondrial DNA data, Nekola et al (2009) showed that Vertigo cristata is not closely related to V. gouldii, with which it had been earlier confused. They also showed that western North American populations with V. cristata-like shell characters are a separate species, V. coloradensis (Cockerell, 1891), from the eastern boreal V. cristata.…”
Section: Family Vertiginidae Genus Vertigo Müller 1774mentioning
confidence: 99%